1966
DOI: 10.1111/j.1550-7408.1966.tb01913.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Various Latex Plants of the Family Asclepiadaceae with Phytomonas elmassiani

Abstract: SYNOPSIS. Trypanosomatid‐free plants of the family Asclepiadaceae identified as Asclepias syriaca, A. curassavica, A. incarnata, Stephanotis floribunda, Seutera maritima, Amphistelma scoparia and plants of the family Euphorbiaceae identified as Euphorbia tirucalli, E. trigona, and Pedilanthus tithymaloides were exposed to the bite of the bug, Oncopeltus fasciatus, infected with Phytomonas elmassiani, a flagellate which occurs naturally in A. syriaca and O. fasciatus. Two weeks subsequent to exposure to labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1971
1971
1994
1994

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…from different host species on morphological characters. Their form may vary according to stages in the life cycle and may depend on the plant species and on the physiological state of the host plant (HANSON et al 1966, MCGHEE and HANSON 1971, DOLLET 1984. In our studies both elongated and rounded forms were found in E. hirta plants, whereas the Phytomonas sp.…”
Section: Discussionsupporting
confidence: 45%
“…from different host species on morphological characters. Their form may vary according to stages in the life cycle and may depend on the plant species and on the physiological state of the host plant (HANSON et al 1966, MCGHEE and HANSON 1971, DOLLET 1984. In our studies both elongated and rounded forms were found in E. hirta plants, whereas the Phytomonas sp.…”
Section: Discussionsupporting
confidence: 45%
“…Complete details of handling of bugs and procedures of infecting them have been previously described (5). Development of the parasite in L. kalmii was similar in all respects to that observed in 0. fasciatus ( 7 ) .…”
Section: Infection Of Hemipterons Was Accomplished By Allowing Just Hmentioning
confidence: 77%
“…At present, only the sucking insects feeding in the laticiferous tubes are known as transmitting agents of flagellates in latex plants (Hanson et al 1966;Ayala et al 1975). For the oil palm, a root-feeding Pentatomidae hemipter (~a c r o~~g i u m reticulare F.) is suspected (Genty 198 l), but the experimental transmission trials have given negative results.…”
Section: Resultsmentioning
confidence: 98%